Vie privée = A private life [videorecording (DVD)] - Coudert, Robin, 1978- (Sony Pictures Classics, 2026)
"When renowned psychiatrist Lilian Steiner learns of the sudden death of a patient, she suspects murder. She mounts a private investigation, enlisting an odd assortment of quirky characters."--